RANCANGAN APLIKASI SISTEM ENKRIPSI DAN DEKRIPSI BERKAS (STUDI KASUS DI SMK TEKNOLOGI INFORMATIKA YPML) - Ahmad Firmansyah; Yolen Perdana Sari (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
This research focuses on the issues of data security and document management at SMK Teknologi Informatika YPML, an educational institution that manages a large number of educational documents. Currently, this institution does not use an encryption system application, which potentially leads to data leaks and other security issues. To address this problem, this research designed an encryption and decryption system application to protect documents and files from unauthorized access. This application is designed by implementing the AES (Rijndael) encryption algorithm capable of encrypting up to 256-bit, so only individuals who have the encryption key can open the document. This research hopes to improve data security and document management efficiency in educational institutions.